Effect of Silvopastoral Systems in the Thermoregulatory and Feeding Behaviors of Water Buffaloes Under Different Conditions of Heat Stress - Galloso-Hernández, Maykel A.; Rodríguez-Estévez, Vicente; Alvarez-Díaz, Carlos A.; Soca-Pérez, Mildrey; Dublin, Devon; Iglesias-Gómez, Jesús; Simon Guelmes, Leonel (Frontiers in Veterinary Science, 2020)
Buffaloes use wallowing behavior to release excess heat in tropical conditions. The aim of this study was to evaluate the impact of silvopastoral systems in the feeding and thermoregulatory behavior of water buffaloes under moderate and intense heat stress. The behavior of water buffaloes was evaluated in two different production systems. The conventional system with Guinea grass (Megathyrsus maximus) only, and the silvopastoral system with Guinea grass and Leucaena leucocephala trees. The relation between the frequency of animal activities and the length of time the animals engaged in each activity was measured during the day time (6:00 to 18:00 hours) by visual observations at 10-minute intervals. The results obtained suggest that buffaloes use tree shade to partially supplement wallowing. Feeding behavior increased under intense heat stress in the silvopastoral system indicating that it can be a promising alternative to improve the buffaloes rearing conditions in the tropics.